Textile bursting strength testing method

By pre-freezing and deep-cooling curing of knitted fabrics, combined with cutting and gradient temperature control methods, the problems of yarn slip and crack position deviation of knitted fabric edges in textile top breaking strength tests were solved, achieving more accurate and reliable test results.

CN119827303AActive Publication Date: 2025-04-15SUZHOU ZHONGKE TEXTILE TECH SERVICE
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510322874.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-15
Estimated Expiration
2045-03-19

AI Technical Summary

Technical Problem

Existing textile top-breaking strength testing methods are prone to problems of edge yarn slip and crack position deviation when testing knitted fabrics.

Method used

The knitted fabric is pre-freezed for 2-3 hours, deep-cooled for 2-5 minutes, and cut and gradient back temperature control after deep-cooled curing, and finally the top-break test is performed on the fixture.

Benefits of technology

Through ultra-low temperature treatment, the fiber molecular segments are transformed from rubber to glass, increasing hardness and cut flatness, reducing slippage and structural offset of the edges of knitted fabrics, and improving the accuracy of the test results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119827303A_ABST
    Figure CN119827303A_ABST
Patent Text Reader

Abstract

The invention discloses a textile bursting strength testing method, and relates to the technical field of testing by means of physical properties of materials, in particular to a testing method for applying stable tension or pressure, which comprises the following steps: sequentially carrying out pre-freezing treatment and cryogenic curing on a knitted fabric, and cutting the knitted fabric after the cryogenic curing is finished. A sample obtained by cutting is heated and then placed on a clamp for bursting testing, the movement capacity of a fiber molecular chain segment is changed at an ultralow temperature, the fiber molecular chain segment is converted into a glassy state from a rubber state, the hardness and the notch smoothness can be improved, the edge of the knitted fabric is smoother, and the product quality is improved. The edge of the knitted fabric is smoother, the offset in the knitted fabric structure is reduced, the retraction rate of the knitted fabric can be reduced after temperature returning, and the problems that in the prior art, edge yarn slippage and fracture position deviation occur when the textile bursting strength is used for testing the knitted fabric are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of testing by means of physical properties of materials, in particular to a testing method of applying stable tension or pressure, and in particular to a method for testing the bursting strength of textiles. Background Art

[0002] The bursting strength test of textiles is a physical indicator used to evaluate the force that textiles withstand when they expand and rupture under the top and pressure of concentrated loads. When a textile is partially subjected to an external force perpendicular to its plane, it will bulge and expand until it ruptures. This phenomenon is called the bursting of the textile, and the force that the textile withstands when it bursts is the bursting strength. It is an indicator to measure the resistance of textiles to local vertical force damage. The specific steps of the steel ball method in the bursting strength test are to clamp a sample of a certain area in a circular sample on a fixed base, and the spherical push rod is pushed vertically against the sample at a constant moving speed, so that the sample is deformed until it ruptures, and the bursting strength is measured. By testing the bursting strength of textiles, we can understand their bursting resistance when subjected to external forces, thereby guiding the design and production of products.

[0003] Knitted fabrics are made of yarns that have a tangle relationship. This tangle relationship is a stable relationship formed by a group of yarns bending left and right, and the adjacent yarns are intertwined. Knitting is a fabric formed by bending the yarns into loops and intertwining them with knitting needles. In this process, the yarns form loops through the regular movement of knitting, and the loops are intertwined with each other to form a knitted fabric.

[0004] In actual testing, cutting the edges of fabrics can easily lead to damage to the yarn structure, especially for elastic or knitted fabrics. The yarns at the edges of the cut specimens are prone to slippage, affecting the accuracy of the test results. Due to the coil structure characteristics of knitted fabrics, they are prone to lateral shrinkage during the clamping process, resulting in uneven force on the specimens. The final rupture position is often concentrated on the edge of the fixture rather than the actual pressure area.

[0005] Therefore, it is necessary to improve the bursting strength test method in the prior art to solve the above problems. Summary of the invention

[0006] The present invention overcomes the shortcomings of the prior art and provides a method for testing the bursting strength of textiles, aiming to solve the problems of edge yarn slippage and rupture position deviation when testing the bursting strength of knitted fabrics in the prior art.

[0007] To achieve the above object, the technical solution adopted by the present invention is: a method for testing the bursting strength of textiles, comprising the following steps: S1: pre-freezing the knitted fabric for 2-3 hours, during which a constant tension is applied; S2: subjecting the knitted fabric to cryogenic curing, wherein the cryogenic curing time is 2-5 minutes; S3: After the cryogenic solidification treatment, the knitted fabric is taken out and cut, and after cutting, a gradient temperature recovery control is performed to obtain a plurality of samples; S4: Place the sample on the fixture, start the spherical push rod to push the sample until the sample is broken, record the maximum bursting strength during the bursting process, perform bursting tests on several samples in turn, and calculate the average value of the maximum bursting strengths obtained for several samples.

[0008] In a preferred embodiment of the present invention, the spandex content in the knitted fabric is 15-20%, and the knitted fabric is a weft knitted fabric.

[0009] In a preferred embodiment of the present invention, the constant tension in S1 is 5-8 N / m, and the direction of the constant tension is along the weft direction of the fabric.

[0010] In a preferred embodiment of the present invention, a vacuum treatment is performed before the pre-freezing treatment in S1, specifically, the knitted fabric is placed under a vacuum degree of 0.1-0.2 Pa for 30-45 minutes.

[0011] In a preferred embodiment of the present invention, the pre-freezing treatment temperature in S1 is -50 to -40°C, and the pre-freezing treatment is covering with dry ice or placing in a freezer.

[0012] In a preferred embodiment of the present invention, the cryogenic solidification temperature in S2 is -150~-120°C, and the cryogenic solidification treatment is liquid nitrogen immersion.

[0013] In a preferred embodiment of the present invention, during the liquid nitrogen immersion process, a load of 20-50 g is evenly loaded on one side of the knitted fabric, and the knitted fabric is vertically immersed in the liquid nitrogen, with the knitted fabric arranged vertically in the weft direction.

[0014] In a preferred embodiment of the present invention, the cutting process in S3 uses a titanium alloy blade with a blade edge pressure of 45-60N / mm 2 , the blade travel speed is 12-15mm / s.

[0015] In a preferred embodiment of the present invention, the gradient temperature recovery control in S3 is to first stand at -80~-70℃ for 30-40min and then increase the temperature to -20℃ at a rate of 0.5℃ / min, then soak in water at a temperature of 20-25℃ for 1-2h and take out to dry.

[0016] In a preferred embodiment of the present invention, the clamping method of the clamp in S4 is double clamping, including inner ring clamping and outer ring clamping, the outer ring clamping shape is square, and the inner ring clamping shape is circular.

[0017] The present invention solves the defects existing in the background technology and has the following beneficial effects: (1) The present invention provides a method for testing the bursting strength of a textile, wherein a knitted fabric is pre-frozen and cryogenically cured in sequence, and the knitted fabric is cut after the cryogenic curing is completed. The cut sample is warmed up and then placed on a fixture for a bursting test. Ultra-low temperature changes the mobility of the fiber molecular chain segments, causing them to change from a rubber state to a glass state. Compared with the bursting strength testing method in the prior art, the method can increase the hardness and the flatness of the cut, making the edge of the knitted fabric smoother and reducing the offset in the knitted fabric structure. After warming up, the knitted fabric shrinkage rate can be reduced, thereby solving the problem of edge yarn slippage and rupture position deviation when testing the bursting strength of knitted fabrics in the prior art.

[0018] (2) In the present invention, a vacuum treatment is performed before the pre-freezing treatment of S1, specifically, the knitted fabric is placed under a vacuum degree of 0.1-0.2 Pa for 30-45 minutes. Impurities such as oxides and dirt on the surface of the knitted fabric are effectively removed under the vacuum environment. Compared with the prior art, this helps to reduce the impact of these impurities on the friction between fibers, thereby reducing the risk of edge yarn slippage.

[0019] (3) In the present invention, during the liquid nitrogen immersion process, a uniform load is applied to one side of the knitted fabric, and the knitted fabric is vertically immersed in the liquid nitrogen. The knitted fabric is vertically arranged in the weft direction. Compared with the prior art, the structure of the fabric can be effectively stabilized, and the internal stress unevenness caused by the free swinging or deformation of the fabric during the liquid nitrogen immersion process can be prevented. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work. Figure 1 It is a method step diagram of a preferred embodiment of the present invention. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0023] Weft knitted fabrics are made of one or more yarns that are knitted in order along the horizontal direction of the fabric and interlaced with each other in the vertical direction. Due to the characteristics of its coil structure, weft knitted fabrics usually have good stretchability and extensibility. This elasticity enables weft knitted fabrics to adapt to body movements and are comfortable to wear. They are particularly suitable for making clothing that requires a certain degree of elasticity, such as sportswear, underwear, etc.

[0024] like Figure 1 As shown, a method for testing the bursting strength of a textile comprises the following steps: S1: The knitted fabric is pre-frozen for 2-3 hours, and a constant tension is applied during the pre-freezing process; the constant tension in the weft direction orients the spandex molecular chains along the force direction, improves the isotropy of the subsequent cryogenic treatment, and puts the material in a metastable state, providing a structural basis for the cryogenic phase transition.

[0025] S2: subjecting the knitted fabric to cryogenic curing, wherein the cryogenic curing time is 2-5 minutes; S3: After the cryogenic solidification treatment, the knitted fabric is taken out and cut, and after cutting, a gradient temperature recovery control is performed to obtain a number of samples; S4: Place the sample on the fixture, start the spherical push rod to push the sample until the sample is broken, record the maximum bursting strength during the bursting process, perform bursting tests on several samples in turn, and calculate the average value of the maximum bursting strengths obtained for several samples.

[0026] The knitted fabric is pre-frozen and cryogenically cured in turn, and then cut after cryogenic curing. The cut samples are warmed up and placed on a fixture for bursting test. Ultra-low temperature changes the mobility of the fiber molecular segments, causing them to change from a rubber state to a glass state, which can increase the hardness and the smoothness of the cut, making the edge of the knitted fabric smoother and reducing the offset within the knitted fabric structure. After warming up, the shrinkage rate of the knitted fabric can be reduced, which solves the problems of edge yarn slippage and rupture position deviation when testing the knitted fabric bursting strength of textiles in the prior art.

[0027] Furthermore, the spandex content in the knitted fabric is 15-20%, and it is a weft knitted fabric. Spandex is an elastic fiber, and its molecular chain segments are in a rubber state at room temperature and have a large elastic deformation capacity. Under low temperature treatment, the molecular chain segments of spandex change from a rubber state to a glass state, lose elastic recovery ability, and help reduce the retraction force caused by elastic deformation during shearing. The tear resistance of weft knitted fabrics is generally better than other types of fabrics, and they can better resist the bursting effect of the ejector rod, reducing the risk of rupture position deviation.

[0028] Furthermore, the constant tension in S1 is 5-8N / m, and the direction of the constant tension is along the weft direction of the fabric. The coil structure in the transverse direction of the weft knitted fabric undergoes uniform tensile deformation, so that the spandex molecular chains are oriented along the force direction. This pre-oriented structure forms an anisotropically enhanced "quasi-lattice" after deep cold curing, so that the rupture energy is more concentratedly transmitted to the test center area. The constant tension direction is set along the weft direction of the fabric, which helps to form a directional stress distribution inside the fabric. During the burst test, this directional stress distribution can guide the rupture to proceed in a predetermined direction, thereby reducing the deviation of the rupture position.

[0029] Furthermore, a vacuum treatment is performed before the pre-freezing treatment of S1, specifically, the knitted fabric is placed under a vacuum degree of 0.1-0.2Pa for 30-45min. In a vacuum environment, impurities such as oxides and dirt on the surface of the knitted fabric are effectively removed, which helps to reduce the impact of these impurities on the friction between fibers, thereby reducing the risk of edge yarn slippage. The vacuum treatment effectively removes the gas and moisture molecules inside the knitted fabric by extracting air and moisture. This can prevent the gas and moisture molecules from expanding or freezing during the ultra-low temperature treatment, causing damage to the fibers, thereby reducing the risk of rupture position deviation. The vacuum treatment helps to keep the molecular segments of the knitted fabric fibers in a relatively stable state before pretreatment. This can reduce the violent movement of the fiber molecular segments in the subsequent ultra-low temperature treatment, help maintain the integrity of the fiber structure, and thus reduce test errors.

[0030] Furthermore, the pre-freezing treatment temperature in S1 is -50~-40℃, and the pre-freezing treatment is covered with dry ice or placed in a freezer. Low temperature causes changes in the microstructure of the yarn surface, such as increased roughness of the fiber surface, thereby increasing the friction between the yarns. This increased friction helps prevent the relative sliding of the yarns during the test, further reducing the slippage of the edge yarns.

[0031] Furthermore, the cryogenic curing temperature in S2 is -150~-120℃, and the cryogenic curing treatment is liquid nitrogen immersion. During the cryogenic curing process, the mobility of the fiber molecular segments decreases, and they change from a rubber state to a glass state. This transformation increases the hardness and cut flatness of the fiber, making the edge of the knitted fabric smoother and reducing the offset within the structure.

[0032] Furthermore, during the liquid nitrogen immersion process, a load of 20-50 g is evenly loaded on one side of the knitted fabric, and the knitted fabric is vertically immersed in the liquid nitrogen, and the knitted fabric is vertically arranged in the weft direction. Evenly loading a load of a certain weight on one side of the knitted fabric can effectively stabilize the structure of the fabric and prevent uneven internal stress caused by free swinging or deformation of the fabric during the liquid nitrogen immersion process.

[0033] Furthermore, the cutting process in S3 uses a titanium alloy blade with a cutting edge pressure of 45-60N / mm 2 , the blade travel speed is 12-15mm / s. Titanium alloy blades have high hardness and wear resistance, which can keep the edge sharp and stable during cutting, helping to reduce friction and resistance during cutting. Setting the edge pressure to 45-60N / mm² can ensure that the blade applies appropriate pressure during cutting. This pressure range can ensure smooth cutting while avoiding excessive damage to knitted fabrics. Appropriate pressure helps to reduce yarn slippage and fabric deformation. Controlling the blade travel speed within the range of 12-15mm / s can ensure a smooth and uniform cutting process. Too fast a travel speed leads to inaccurate cutting or yarn slippage, while too slow a speed increases cutting time and friction resistance.

[0034] Furthermore, the gradient temperature recovery control in S3 is to first stand at -80~-70℃ for 30-40min, then increase the temperature to -20℃ at a rate of 0.5℃ / min, and then soak in water at a temperature of 20-25℃ for 1-2h and take out to dry. Slowly heating to -20℃ at a rate of 0.5℃ / min can gradually release the stress accumulated in the knitted fabric at low temperature. This step helps to avoid the internal stress concentration caused by the rapid temperature change of the fabric, thereby reducing the risk of yarn slippage and rupture. Soaking the fabric in water at a temperature of 20-25℃ for 1-2 hours can gradually restore the fiber to its performance state at room temperature. This step helps to restore the elasticity and toughness of the fiber.

[0035] Furthermore, the clamping method of the fixture in S4 is double clamping, including inner ring clamping and outer ring clamping, the outer ring clamping shape is square, and the inner ring clamping shape is circular. The double clamping method can fix the knitted fabric more stably and reduce the slippage during the test by clamping the inner and outer rings at the same time. The inner ring circular clamping can provide uniform radial pressure, while the outer ring square clamping can prevent the relative movement of the fabric in the test direction. The combination of the two greatly enhances the stability of the clamping. The square clamping shape can better adapt to the structural characteristics of knitted fabrics, especially in biaxial tensile tests. The square clamping can provide uniform clamping force in four directions, which helps to prevent the fabric from slipping in any direction during the test. The circular clamping shape can provide a more uniform radial pressure distribution, which helps to reduce the stress concentration inside the fabric. In the bursting strength test, the circular clamping can better simulate the actual situation of the fabric under stress, making the test results closer to the true value.

[0036] The glassy material has higher uniformity, and the pre-freezing and vacuum treatment further reduce the internal defects of the fiber, making the pressure distribution of the clamp more uniform and avoiding edge loosening caused by local stress concentration.

[0037] When the rubber-state spandex is clamped, it will produce a retraction force due to elastic deformation, resulting in continuous dynamic stress in the clamping area, which is easy to cause progressive slip. However, the material in the glass state has no elastic recovery ability, and the deformation is fixed after clamping, avoiding slip caused by the retraction force.

[0038] Embodiment 1

[0039] This embodiment provides a method for testing the bursting strength of a textile, comprising the following steps: S1: a weft knitted fabric with a spandex content of 15% was placed in a vacuum of 0.05 Pa for 45 min, and then pre-frozen for 2 h. The pre-freezing temperature was -40 °C, and the pre-freezing was covered with dry ice. A constant tension was applied during the pre-freezing process. The constant tension was 6 N / m, and the direction of the constant tension was along the weft direction of the fabric. S2: cryogenically curing the knitted fabric, the cryogenic curing time is 3 minutes, the cryogenic curing temperature is -120°C, the cryogenic curing treatment is liquid nitrogen immersion, during the liquid nitrogen immersion, a load of 40g is evenly loaded on one side of the knitted fabric, the knitted fabric is vertically immersed in the liquid nitrogen, and the knitted fabric is vertically arranged in the weft direction; S3: After cryogenic curing, the knitted fabric is taken out and cut. Titanium alloy blades are used in the cutting process, and the edge pressure is 60N / mm 2The blade travel speed is 15 mm / s. After cutting, the sample is subjected to gradient temperature recovery control. The gradient temperature recovery control is to first stand at -70°C for 40 minutes and then increase the temperature to -20°C at a rate of 0.5°C / min. Then, the sample is immersed in water at 25°C for 2 hours and then taken out and dried to obtain several samples. S4: Place the sample on the fixture. The clamping method of the fixture is double clamping, including inner ring clamping and outer ring clamping. The outer ring clamping shape is square and the inner ring clamping shape is circular. Start the spherical push rod to push the sample until the sample is broken. Record the maximum bursting strength during the bursting process. Perform bursting tests on several samples in turn and calculate the average value of the maximum bursting strengths obtained for several samples.

[0040] Embodiment 2

[0041] This embodiment provides a method for testing the bursting strength of a textile, comprising the following steps: S1: a weft knitted fabric with a spandex content of 15% was placed in a vacuum of 0.1 Pa for 45 min, and then pre-frozen for 2 h. The pre-freezing temperature was -40 °C, and the pre-freezing was covered with dry ice. A constant tension was applied during the pre-freezing process. The constant tension was 6 N / m, and the direction of the constant tension was along the weft direction of the fabric. S2: cryogenically curing the knitted fabric, the cryogenic curing time is 3 minutes, the cryogenic curing temperature is -120°C, the cryogenic curing treatment is liquid nitrogen immersion, during the liquid nitrogen immersion, a load of 40g is evenly loaded on one side of the knitted fabric, the knitted fabric is vertically immersed in the liquid nitrogen, and the knitted fabric is vertically arranged in the weft direction; S3: After cryogenic curing, the knitted fabric is taken out and cut. Titanium alloy blades are used in the cutting process, and the edge pressure is 60N / mm 2 The blade travel speed is 15 mm / s. After cutting, the sample is subjected to gradient temperature recovery control. The gradient temperature recovery control is to first stand at -70°C for 40 minutes and then increase the temperature to -20°C at a rate of 0.5°C / min. Then, the sample is immersed in water at 25°C for 2 hours and then taken out and dried to obtain several samples. S4: Place the sample on the fixture. The clamping method of the fixture is double clamping, including inner ring clamping and outer ring clamping. The outer ring clamping shape is square and the inner ring clamping shape is circular. Start the spherical push rod to push the sample until the sample is broken. Record the maximum bursting strength during the bursting process. Perform bursting tests on several samples in turn and calculate the average value of the maximum bursting strengths obtained for several samples.

[0042] Embodiment 3

[0043] This embodiment provides a method for testing the bursting strength of a textile, comprising the following steps: S1: a weft knitted fabric with a spandex content of 15% was placed in a vacuum of 0.15 Pa for 45 min, and then pre-frozen for 2 h. The pre-freezing temperature was -40 °C, and the pre-freezing was covered with dry ice. A constant tension was applied during the pre-freezing process. The constant tension was 6 N / m, and the direction of the constant tension was along the weft direction of the fabric. S2: cryogenically curing the knitted fabric, the cryogenic curing time is 3 minutes, the cryogenic curing temperature is -120°C, the cryogenic curing treatment is liquid nitrogen immersion, during the liquid nitrogen immersion, a load of 40g is evenly loaded on one side of the knitted fabric, the knitted fabric is vertically immersed in the liquid nitrogen, and the knitted fabric is vertically arranged in the weft direction; S3: After cryogenic curing, the knitted fabric is taken out and cut. Titanium alloy blades are used in the cutting process, and the edge pressure is 60N / mm 2 The blade travel speed is 15 mm / s. After cutting, the sample is subjected to gradient temperature recovery control. The gradient temperature recovery control is to first stand at -70°C for 40 minutes and then increase the temperature to -20°C at a rate of 0.5°C / min. Then, the sample is immersed in water at 25°C for 2 hours and then taken out and dried to obtain several samples. S4: Place the sample on the fixture. The clamping method of the fixture is double clamping, including inner ring clamping and outer ring clamping. The outer ring clamping shape is square and the inner ring clamping shape is circular. Start the spherical push rod to push the sample until the sample is broken. Record the maximum bursting strength during the bursting process. Perform bursting tests on several samples in turn and calculate the average value of the maximum bursting strengths obtained for several samples.

[0044] Embodiment 4

[0045] This embodiment provides a method for testing the bursting strength of a textile, comprising the following steps: S1: a weft knitted fabric with a spandex content of 15% was placed in a vacuum of 0.2 Pa for 45 min, and then pre-frozen for 2 h. The pre-freezing temperature was -40 °C, and the pre-freezing was covered with dry ice. A constant tension was applied during the pre-freezing process. The constant tension was 6 N / m, and the direction of the constant tension was along the weft direction of the fabric. S2: cryogenically curing the knitted fabric, the cryogenic curing time is 3 minutes, the cryogenic curing temperature is -120°C, the cryogenic curing treatment is liquid nitrogen immersion, during the liquid nitrogen immersion, a load of 40g is evenly loaded on one side of the knitted fabric, the knitted fabric is vertically immersed in the liquid nitrogen, and the knitted fabric is vertically arranged in the weft direction; S3: After cryogenic curing, the knitted fabric is taken out and cut. Titanium alloy blades are used in the cutting process, and the edge pressure is 60N / mm 2The blade travel speed is 15 mm / s. After cutting, the sample is subjected to gradient temperature recovery control. The gradient temperature recovery control is to first stand at -70°C for 40 minutes and then increase the temperature to -20°C at a rate of 0.5°C / min. Then, the sample is immersed in water at 25°C for 2 hours and then taken out and dried to obtain several samples. S4: Place the sample on the fixture. The clamping method of the fixture is double clamping, including inner ring clamping and outer ring clamping. The outer ring clamping shape is square and the inner ring clamping shape is circular. Start the spherical push rod to push the sample until the sample is broken. Record the maximum bursting strength during the bursting process. Perform bursting tests on several samples in turn and calculate the average value of the maximum bursting strengths obtained for several samples.

[0046] Embodiment 5

[0047] This embodiment provides a method for testing the bursting strength of a textile, comprising the following steps: S1: a weft knitted fabric with a spandex content of 15% was placed in a vacuum of 0.25 Pa for 45 min, and then pre-frozen for 2 h. The pre-freezing temperature was -40 °C, and the pre-freezing was covered with dry ice. A constant tension was applied during the pre-freezing process. The constant tension was 6 N / m, and the direction of the constant tension was along the weft direction of the fabric. S2: cryogenically curing the knitted fabric, the cryogenic curing time is 3 minutes, the cryogenic curing temperature is -120°C, the cryogenic curing treatment is liquid nitrogen immersion, during the liquid nitrogen immersion, a load of 40g is evenly loaded on one side of the knitted fabric, the knitted fabric is vertically immersed in the liquid nitrogen, and the knitted fabric is vertically arranged in the weft direction; S3: After cryogenic curing, the knitted fabric is taken out and cut. Titanium alloy blades are used in the cutting process, and the edge pressure is 60N / mm 2 The blade travel speed is 15 mm / s. After cutting, the sample is subjected to gradient temperature recovery control. The gradient temperature recovery control is to first stand at -70°C for 40 minutes and then increase the temperature to -20°C at a rate of 0.5°C / min. Then, the sample is immersed in water at 25°C for 2 hours and then taken out and dried to obtain several samples. S4: Place the sample on the fixture. The clamping method of the fixture is double clamping, including inner ring clamping and outer ring clamping. The outer ring clamping shape is square and the inner ring clamping shape is circular. Start the spherical push rod to push the sample until the sample is broken. Record the maximum bursting strength during the bursting process. Perform bursting tests on several samples in turn and calculate the average value of the maximum bursting strengths obtained for several samples.

[0048] Embodiment 6

[0049] This embodiment provides a method for testing the bursting strength of a textile, comprising the following steps: S1: a weft knitted fabric with a spandex content of 15% was placed in a vacuum of 0.15 Pa for 45 min, and then pre-frozen for 2 h. The pre-freezing temperature was -40 °C, and the pre-freezing was covered with dry ice. A constant tension was applied during the pre-freezing process. The constant tension was 6 N / m, and the direction of the constant tension was along the weft direction of the fabric. S2: cryogenically curing the knitted fabric, the cryogenic curing time is 3 minutes, the cryogenic curing temperature is -105°C, the cryogenic curing treatment is liquid nitrogen immersion, during the liquid nitrogen immersion, a load of 40g is evenly loaded on one side of the knitted fabric, and the knitted fabric is vertically immersed in the liquid nitrogen, and the knitted fabric is arranged vertically in the weft direction; S3: After cryogenic curing, the knitted fabric is taken out and cut. Titanium alloy blades are used in the cutting process, and the edge pressure is 60N / mm 2 The blade travel speed is 15 mm / s. After cutting, the sample is subjected to gradient temperature recovery control. The gradient temperature recovery control is to first stand at -70°C for 40 minutes and then increase the temperature to -20°C at a rate of 0.5°C / min. Then, the sample is immersed in water at 25°C for 2 hours and then taken out and dried to obtain several samples. S4: Place the sample on the fixture. The clamping method of the fixture is double clamping, including inner ring clamping and outer ring clamping. The outer ring clamping shape is square and the inner ring clamping shape is circular. Start the spherical push rod to push the sample until the sample is broken. Record the maximum bursting strength during the bursting process. Perform bursting tests on several samples in turn and calculate the average value of the maximum bursting strengths obtained for several samples.

[0050] Embodiment 7

[0051] This embodiment provides a method for testing the bursting strength of a textile, comprising the following steps: S1: a weft knitted fabric with a spandex content of 15% was placed in a vacuum of 0.15 Pa for 45 min, and then pre-frozen for 2 h. The pre-freezing temperature was -40 °C, and the pre-freezing was covered with dry ice. A constant tension was applied during the pre-freezing process. The constant tension was 6 N / m, and the direction of the constant tension was along the weft direction of the fabric. S2: cryogenically curing the knitted fabric, the cryogenic curing time is 3 minutes, the cryogenic curing temperature is -135°C, the cryogenic curing treatment is liquid nitrogen immersion, during the liquid nitrogen immersion, a load of 40g is evenly loaded on one side of the knitted fabric, the knitted fabric is vertically immersed in the liquid nitrogen, and the knitted fabric is vertically arranged in the weft direction; S3: After cryogenic curing, the knitted fabric is taken out and cut. Titanium alloy blades are used in the cutting process, and the edge pressure is 60N / mm 2The blade travel speed is 15 mm / s. After cutting, the sample is subjected to gradient temperature recovery control. The gradient temperature recovery control is to first stand at -70°C for 40 minutes and then increase the temperature to -20°C at a rate of 0.5°C / min. Then, the sample is immersed in water at 25°C for 2 hours and then taken out and dried to obtain several samples. S4: Place the sample on the fixture. The clamping method of the fixture is double clamping, including inner ring clamping and outer ring clamping. The outer ring clamping shape is square and the inner ring clamping shape is circular. Start the spherical push rod to push the sample until the sample is broken. Record the maximum bursting strength during the bursting process. Perform bursting tests on several samples in turn and calculate the average value of the maximum bursting strengths obtained for several samples.

[0052] Embodiment 8

[0053] This embodiment provides a method for testing the bursting strength of a textile, comprising the following steps: S1: a weft knitted fabric with a spandex content of 15% was placed in a vacuum of 0.15 Pa for 45 min, and then pre-frozen for 2 h. The pre-freezing temperature was -40 °C, and the pre-freezing was covered with dry ice. A constant tension was applied during the pre-freezing process. The constant tension was 6 N / m, and the direction of the constant tension was along the weft direction of the fabric. S2: cryogenically curing the knitted fabric, the cryogenic curing time is 3 minutes, the cryogenic curing temperature is -150°C, the cryogenic curing treatment is liquid nitrogen immersion, during the liquid nitrogen immersion, a load of 40g is evenly loaded on one side of the knitted fabric, and the knitted fabric is vertically immersed in the liquid nitrogen, and the knitted fabric is arranged vertically in the weft direction; S3: After cryogenic curing, the knitted fabric is taken out and cut. Titanium alloy blades are used in the cutting process, and the edge pressure is 60N / mm 2 The blade travel speed is 15 mm / s. After cutting, the sample is subjected to gradient temperature recovery control. The gradient temperature recovery control is to first stand at -70°C for 40 minutes and then increase the temperature to -20°C at a rate of 0.5°C / min. Then, the sample is immersed in water at 25°C for 2 hours and then taken out and dried to obtain several samples. S4: Place the sample on the fixture. The clamping method of the fixture is double clamping, including inner ring clamping and outer ring clamping. The outer ring clamping shape is square and the inner ring clamping shape is circular. Start the spherical push rod to push the sample until the sample is broken. Record the maximum bursting strength during the bursting process. Perform bursting tests on several samples in turn and calculate the average value of the maximum bursting strengths obtained for several samples.

[0054] Embodiment 9

[0055] This embodiment provides a method for testing the bursting strength of a textile, comprising the following steps: S1: a weft knitted fabric with a spandex content of 15% was placed in a vacuum of 0.15 Pa for 45 min, and then pre-frozen for 2 h. The pre-freezing temperature was -40 °C, and the pre-freezing was covered with dry ice. A constant tension was applied during the pre-freezing process. The constant tension was 6 N / m, and the direction of the constant tension was along the weft direction of the fabric. S2: cryogenically curing the knitted fabric, the cryogenic curing time is 3 minutes, the cryogenic curing temperature is -165°C, the cryogenic curing treatment is liquid nitrogen immersion, during the liquid nitrogen immersion, a load of 40g is evenly loaded on one side of the knitted fabric, the knitted fabric is vertically immersed in the liquid nitrogen, and the knitted fabric is vertically arranged in the weft direction; S3: After cryogenic curing, the knitted fabric is taken out and cut. Titanium alloy blades are used in the cutting process, and the edge pressure is 60N / mm 2 The blade travel speed is 15 mm / s. After cutting, the sample is subjected to gradient temperature recovery control. The gradient temperature recovery control is to first stand at -70°C for 40 minutes and then increase the temperature to -20°C at a rate of 0.5°C / min. Then, the sample is immersed in water at 25°C for 2 hours and then taken out and dried to obtain several samples. S4: Place the sample on the fixture. The clamping method of the fixture is double clamping, including inner ring clamping and outer ring clamping. The outer ring clamping shape is square and the inner ring clamping shape is circular. Start the spherical push rod to push the sample until the sample is broken. Record the maximum bursting strength during the bursting process. Perform bursting tests on several samples in turn and calculate the average value of the maximum bursting strengths obtained for several samples.

[0056] Comparative Example 1 This comparative example provides a method for testing the bursting strength of a textile, comprising the following steps: S1: Cutting weft knitted fabric with 15% spandex content, using titanium alloy blades with a blade pressure of 60N / mm 2 , the blade travel speed is 15 mm / s, and several samples are obtained; S4: Place the sample on the fixture, start the spherical push rod to push the sample until the sample is broken, record the maximum bursting strength during the bursting process, perform bursting tests on several samples in turn, and calculate the average value of the maximum bursting strengths obtained for several samples.

[0057] The bursting strength test was carried out by the test methods of Examples 1 to 9 and Comparative Example 1, and the sample slippage and rupture position deviation during the test were compared. When sampling the sample slippage, 4 fluorescent marking points were symmetrically sprayed on the outer edge of the sample. The marking point positions were: 0°, 90°, 180°, and 270°. The displacement of the marking points was recorded throughout the bursting test. The radial slippage was calculated with the geometric center of the sample as the coordinate origin. The slippage was the maximum value of the displacement of the 4 marking points at the moment of bursting. The slippage calculation formula is: , is the maximum displacement of each marking point, i is the marking point number, (x 0 ,y 0 ) and (x i ,y i ) are the coordinates of the initial marking point and the coordinates of the maximum displacement, and the average slip value is taken to obtain the sample slip; the rupture position deviation is the deviation distance between the rupture position and the predetermined center. The sample slip and rupture position deviation are shown in Table 1.

[0058] Table 1 Data on the slippage and rupture position deviation of samples of Examples 1 to 9 and Comparative Example 1

[0059] It can be seen from Table 1 that the slippage and rupture position deviation of the samples of Examples 1 to 9 are smaller than those of the sample of Comparative Example 1, and they have better anti-slip performance and rupture position accuracy, and are superior.

[0060] In Examples 1 to 5, as the vacuum degree gradually increases, the sample slippage and the rupture position deviation first decrease and then increase, and the anti-slip performance and the rupture position accuracy first increase and then weaken. This is because as the vacuum degree gradually increases, the vacuum treatment can make the fabric more evenly stressed during the test, reduce the stress concentration phenomenon caused by the uneven fabric structure, and improve the accuracy and reliability of the test results. When the vacuum degree is too low, the moisture in the fiber will form ice crystals during the cooling process, and the fiber performance will be affected when it is warmed up, causing the internal defects of the fiber to increase. When the vacuum degree is too high, the air inside the fabric will be excessively extracted, resulting in reduced elasticity between the fibers, and poor flexibility and adaptability of the fabric. When stressed, the fabric cannot disperse stress as evenly as it does under a lower vacuum degree, and the stress concentration phenomenon in some areas is aggravated, thereby affecting the accuracy of the test results. The preferred embodiment is Example 3.

[0061] In Example 3 and Examples 6 to 9, as the temperature of cryogenic solidification decreases, the sample slippage and the deviation of the fracture position first decrease and then increase, and the anti-slip performance and the accuracy of the fracture position first increase and then weaken. This is because during the cryogenic solidification process, as the temperature decreases, the fabric fibers will shrink and rearrange, which helps the fibers to be arranged more tightly and orderly, and can reduce residual stress, which helps to improve the stability and uniformity of the fabric, thereby enhancing the anti-slip performance and the accuracy of the fracture position, thereby reducing the slippage of the fabric when it is stressed and the deviation of the fracture position. However, when the temperature is too low, the fibers will become too fragile and brittle, making it easier to break and slip locally when stressed, and will cause new residual stress to be generated, which is not conducive to the performance of the fabric, thereby increasing the slippage and the deviation of the fracture position. The preferred embodiment is Example 7.

[0062] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.

Claims

1. A method for testing the bursting strength of a textile, characterized in that: The following steps are involved: S1: pre-freezing the knitted fabric for 2-3 hours, during which a constant tension is applied; S2: subjecting the knitted fabric to cryogenic curing, wherein the cryogenic curing time is 2-5 minutes; S3: After the cryogenic solidification treatment, the knitted fabric is taken out and cut, and after cutting, a gradient temperature recovery control is performed to obtain a plurality of samples; S4: Place the sample on the fixture, start the spherical push rod to push the sample until the sample is broken, record the maximum bursting strength during the bursting process, perform bursting tests on several samples in turn, and calculate the average value of the maximum bursting strengths obtained for several samples.

2. A method for testing the bursting strength of textiles according to claim 1, characterized in that: The spandex content in the knitted fabric is 15-20%, and the knitted fabric is a weft knitted fabric.

3. A method for testing the bursting strength of textiles according to claim 2, characterized in that: The constant tension in S1 is 5-8 N / m, and the direction of the constant tension is along the weft direction of the fabric.

4. A method for testing the bursting strength of textiles according to claim 1, characterized in that: Before the pre-freezing treatment in S1, a vacuum treatment is performed, specifically, the knitted fabric is placed under a vacuum degree of 0.1-0.2 Pa for 30-45 minutes.

5. A method for testing the bursting strength of textiles according to claim 1, characterized in that: The pre-freezing treatment temperature in S1 is -50 to -40°C, and the pre-freezing treatment is covered with dry ice or placed in a freezer.

6. A method for testing the bursting strength of textiles according to claim 1, characterized in that: The cryogenic solidification temperature in S2 is -150 to -120° C., and the cryogenic solidification treatment is liquid nitrogen immersion.

7. A method for testing the bursting strength of textiles according to claim 6, characterized in that: During the liquid nitrogen immersion process, a load of 20-50 g is evenly loaded on one side of the knitted fabric, and the knitted fabric is vertically immersed in the liquid nitrogen, with the knitted fabric being arranged vertically in the weft direction.

8. A method for testing the bursting strength of textiles according to claim 1, characterized in that: The cutting process in S3 uses a titanium alloy blade with a cutting edge pressure of 45-60N / mm 2 , the blade travel speed is 12-15mm / s.

9. A method for testing the bursting strength of textiles according to claim 1, characterized in that: The gradient temperature recovery in S3 is controlled by first standing at -80~-70°C for 30-40 minutes and then heating to -20°C at a rate of 0.5°C / min, then soaking in water at a temperature of 20-25°C for 1-2 hours and taking out to dry.

10. A method for testing the bursting strength of textiles according to claim 1, characterized in that: The clamping method of the clamp in S4 is double clamping, including inner ring clamping and outer ring clamping, the outer ring clamping shape is square, and the inner ring clamping shape is circular.

Citation Information

Patent Citations

  • Preparation method of modified polyimide fibers

    CN106012490A

  • Method for modifying polyamide fabric

    CN108951117A

  • Method for testing tensile breaking strength of carbon fiber fabric

    CN112730064A

  • Knitted fabric processing technology

    CN114771039A

  • Method for testing tensile breaking strength of carbon fiber fabric and application thereof

    CN118392659A